Efficient in-situ synthesis of heterocyclic derivatives from benzyl alcohols using pyrazinium chlorochromate-functionalized carbonitride as a novel catalyst - Hasan Soltani; Zeinab Tajik; Zahra Nasri; Peyman Hanifehnejad; Elaheh Hamidi; Zahra Aslbeigi; Hossein Ghafuri (Scientific Reports)
Abstract The synthesis of efficient organic compounds from simple substrates is both noticeable and important. However, it can be challenging to achieve this target using suitable strategies. To address this issue, pyrazinium chlorochromate (PCC) was used to modify carbonitride nanosheets (CNs) and applied as a heterogeneous catalyst in the oxidation of benzyl alcohols. That can be regarded as innovation in ingenious synthesis of the PCC on the CNs. Then, it was identified by varied techniques such as EDS, FT-IR, XRD, STA and FE-SEM. This process resulted in in-situ synthesis of 1,4-dihydropyridine and 3,4-dihydropyrimidin-2-(1H) one derivatives with excellent yield.